Teologi Perjamuan Kudus menurut Kaum Anabaptis, Zwingli, dan Calvin: dalam Sejarah Reformasi [Theology of Holy Communion According to the Anabaptists, Zwingli, and Calvin: In the History of the Reformation] - Denny Rope (Diligentia: Journal of Theology and Christian Education, 2023)
The 5th century was a bleak time for the development of the church. The Bishop of Rome showed his supremacy over all churches and teachings, which led to the Reformation and the concept of Holy Communion. Holy Communion or Eucharist is interpreted as a form of Jesus' sacrifice accepted by His people through the fellowship of food and drink, namely the body (bread) and blood (wine). This raises the question of whether there is the presence of Christ Jesus in the food and drink or is it just a symbol. This research is to look at the views of reformer theologians Ulrich Zwingli, John Calvin and the Anabaptists on Holy Communion. The results of this study show that there are differences in understanding of Holy Communion. The Anabaptists understood the Supper in almost the same context as Zwingli, namely as a memorial without the presence of Christ. While John Calvin thought that Christ was present in the revelation of His Spirit to awaken His people to the work of salvation. The thing that makes their views on Eucharist theology the same is the excavation carried out based on the Word of God. The renewed understanding of Holy Communion is inseparable from the teaching of the Roman Catholic Church at that time which seemed to show its superiority where the Eucharist was considered the way for humans to get forgiveness of sins. The focus of Holy Communion can be understood as God's action to reveal the concept of Jesus' sacrifice as the powerful Christ, ruling through His Spirit and working in His members.  And the specific meaning for His people today is to remember, repent, and have faith in Jesus as Lord and Savior.